2012
DOI: 10.1093/molehr/gas043
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 influences trophoblast immune evasion and emerges as a predictive factor for the outcome of pregnancy

Abstract: Galectin-1 (gal-1) is expressed at the feto-maternal interface and plays a role in regulating the maternal immune response against placental alloantigens, contributing to pregnancy maintenance. Both decidua and placenta contribute to gal-1 expression and may be important for the maternal immune regulation. The expression of gal-1 within the placenta is considered relevant to cell-adhesion and invasion of trophoblasts, but the role of gal-1 in the immune evasion machinery exhibited by trophoblast cells remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
120
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(129 citation statements)
references
References 61 publications
6
120
1
2
Order By: Relevance
“…Furthermore, recent studies have demonstrated that Gal-1 regulates trophoblast invasion, differentiation, and immunomodulatory functions (such as HLA-G expression) in vitro (10,13,14). Therefore, it is attractive to speculate that defective Gal-1 expression contributes to the impaired placentation and vascular abnormalities observed in anginex-treated or Lgals1 KO placentas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, recent studies have demonstrated that Gal-1 regulates trophoblast invasion, differentiation, and immunomodulatory functions (such as HLA-G expression) in vitro (10,13,14). Therefore, it is attractive to speculate that defective Gal-1 expression contributes to the impaired placentation and vascular abnormalities observed in anginex-treated or Lgals1 KO placentas.…”
Section: Discussionmentioning
confidence: 99%
“…(ii) prevent a normal placentation (10,13,14), (iii) abrogate maternal immune tolerance toward fetal antigens (11,12), and (iv) threaten gestation by favoring the development of PE, implying that Gal-1 function is essential for a healthy gestation. Anomalies in Gal-1 circulating levels or alteration of Gal-1 expression in the placental villi have been associated with the physiopathology of early pregnancy loss (10,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is of interest to note that EVT cell invasion is increased by both gal-1 (Kolundzic et al, 2011b) and EVs from cytotrophoblast cells grown in a hypoxic environment (Salomon et al, 2013). Both gal-1 (Blois et al, 2007;Tirado-Gonzalez et al, 2013) and placental EVs (Stenqvist et al, 2013;Mincheva-Nilsson and Baranov, 2014;Tannetta et al, 2014) are involved in immunoregulation during pregnancy. As for gal-3 and gal-8, their role in trophoblasts is still unresolved.…”
Section: Discussionmentioning
confidence: 99%